Video Promosi Warung Gunung Kubua Jawi, Sungai Kamuyang, Kecamatan Luak, Kabupaten Lima Puluh Kota - Wahyu Aulia; Eliya Pebriyeni (Departement of Mathematics Education, 2023)
Warung Gunung Kubua Jawi, is one of the first cafes with an open design located on the slopes of Mount Sago, on the Kamuyang River, Luak District, Fifty City District. This cafe does not yet have promotional media that are informative, communicative and effective so that the promotion of this cafe is still inferior compared to other cafes that have done promotions earlier, this is a threat to the sustainability of this business, therefore it needs a promotional media in the form of videos through social media, especially Kubua Jawi's Instagram so it's easy to reach a broad target audience. The aim of the design is to create an information media that is able to give a good image to the cafe, as well as to become an informative, communicative and effective promotional media so that it can reach a broad target audience at minimal cost. The design method used is the 4D (four-D) method. Data collection methods through observation, documentation, interviews, books, scientific journals and the internet. Methods of data analysis with the SWOT method. The results of designing a promotional video for Warung Gunung Kubua Jawi with a duration of 1 minute 30 seconds have been tested for its feasibility to several audiences, both from designers and videographers as well as the general public, this promotional video is published via the Instagram account @kubuajawi_, supporting media in the form of Instagram feeds, posters, x-banners, menu designs, aprons, lanyards, and stickers.